Розроблення установки шліфування фаски на кремнієвих пластинах - Гринь, Михайло Віталійович; Hryn, Mykhailo Vitaliiovych (Національний університет "Львівська політехніка", 2024)
Робота містить пояснювальну записку та графічну частину. Поясню-вальна записка складається зі вступу, технологічної, конструкторської час-тин, додатків з: економічною частиною, охороною праці та специфікаціями до графічної частини. У технологічній частині проаналізований технологічний процес ви-готовлення напівпровідникових пластин [1]. В технологічному маршруті виготовлення пластин передбачені такі операції як калібрування (кругле шліфування) злитку по діаметру, криста-лографічне орієнтування і виготовлення базового зрізу, зняття фаски по діаметру та фінішне багатоступінчасте очищення пластин. Проведений аналіз обладнання для механічної обробки пластин. Представлена схема зняття фаски на напівпровідниковій пластині. Фаски знімають для: усунення сколів, які виникли при відрізанні пластин зі злитка та запобігання їх появи при подальших технологічних операціях; усунення можливості наростання “корони” на краях пластини при прове-денні хіміко-технологічних операцій. Розміри фаски залежать від товщини напівпровідникової пластини. Зняття фаски на напівпровідниковій пластині здійснюється фрезою певного профілю з алмазним покриттям ріжучої поверхні при високій лінійній швидкості ( v = 1600 …1700 м/хв.). У конструкторській частині приведено опис конструкції та принципу дії установки зняття фаски на напівпровідникових пластинах. Машина для шліфування фасок має такі основні робочі органи: шпи-ндель з робочим столиком для утримання пластини і надання їй головного робочого руху - обертання відносно вертикальної осі в процесі обробки; супорт, який призначений для закріплення інструменту і подачі його у зо-ну обробки пластини; позиціонер для юстування заготовки відносно копі-ра; привід головного руху – обертання шпинделя; привід подачі – пово-рот супорта відносно вертикальної осі; привід позиціонера. Проведений розрахунок кінематичної та пневматичної схем машини, розрахунок потужності приводу шпинделя та інструменту, розраховані вакуумний столик для закріплення пластини діаметром dп3 = 100 мм, прое-ктний розрахунок поршневого пневмоциліндра відведення супорту [2,3]. В графічній частині проекту приведені кінематична та пневматичні схеми машини, загальний вид машини, шпиндель, супорт, робочі креслен-ня двох деталей, специфікації до складального креслення. В економічній частині визначена економічність машини для у виго-товленні та експлуатації, визначена доцільність його розробки. В розділі «Охорона праці» розроблені заходи по покращенню робо-ти установки шліфування фаски на кремнієвих пластинах з точки зору тех-ніки безпеки.

The bachelor's qualification work includes a graphic part and an explanatory note. The explanatory note of the bachelor's qualification work consists of an introduction, technological, design and economic parts, a section on labor protection. Literature and specifications for the drawings of assembly units are given. The technological part analyzes the technological process of manufacturing semiconductor wafers [1]. The technological route for manufacturing wafers provides for such operations as calibration (circular grinding) of the ingot by diameter, crystallographic orientation and manufacturing of the base cut, chamfering by diameter and final multi-stage cleaning of the wafers. The analysis of equipment for mechanical processing of wafers is carried out. The scheme of chamfering on a semiconductor wafer is presented. Chamfers are removed to: eliminate chips that occurred when cutting wafers from an ingot and prevent their appearance during subsequent technological operations; eliminate the possibility of a “crown” growing on the edges of the wafer when performing chemical and technological operations. The dimensions of the chamfer depend on the thickness of the semiconductor wafer. Chamfering on a semiconductor wafer is carried out by a milling cutter of a certain profile with a diamond coating of the cutting surface at a high linear speed ( v = 1600 ... 1700 m / min.). The design part describes the design and principle of operation of the chamfering installation on semiconductor wafers. The chamfering machine has the following main working parts: a spindle with a work table for holding the wafer and giving it the main working movement - rotation relative to the vertical axis during processing; a support, which is designed to fix the tool and feed it into the plate processing zone; a positioner for adjusting the workpiece relative to the copier; the main motion drive - spindle rotation; the feed drive - support rotation relative to the vertical axis; the positioner drive. The calculation of the kinematic and pneumatic schemes of the machine was carried out, the calculation of the power of the spindle and tool drive was calculated, a vacuum table for fixing the plate with a diameter of dп3 = 100 mm was calculated, and a design calculation of the piston pneumatic cylinder of the support withdrawal [2,3] was made. The graphic part of the project shows the kinematic and pneumatic schemes of the machine, the general view of the machine, the spindle, the support, working drawings of two parts, specifications for the assembly drawing. In the economic part, the economy of the machine for manufacturing and operation is determined, and the feasibility of its development is determined. In the section "Occupational Safety" measures have been developed to improve the operation of the chamfer grinding unit on silicon wafers from the point of view of safety technology.
Development of a chamfer grinding unit on silicon wafers
Keywords: 6.133.00.00; – напівпровідник; кремній; пластина; фаска; установка; привід; розрахунок; економіка; безпека; - semiconductor; silicon; wafer; chamfer; unit; drive; calculation; economics; safety. List of used literature sources: 1. Pavlov; S. M. P12 Technology of microelectronic devices: a tutorial. / S. M. Pavlov; O. V. Voitsekhovska. - Vinnytsia: VNTU; 2017. - 169 p. 2. Kodra Yu.V.; Stotsko Z.A. Technological machines. Calculation and design: Tutorial / Ed. Z.A. Stotsko. Second edition; supplemented. - Lviv: Publishing house "Beskyd Bit"; 2004. - 466 p. 3. Pavlyshche V.T. Fundamentals of design and calculation of machine parts. – Kyiv: Higher School; 1993. – 556 p